ANALISIS ISLAMIC MARKETING DAN KEPERCAYAAN TERHADAP LOYALITAS NASABAH PADA PT. BANK PEMBIAYAAN RAKYAT SYARIAH (BPRS) LAMPUNG - Ditta Nur Hidayanti (Jurnal At Taajir, 2021)
The high growth rate of the Islamic banking industry is inseparable from the expansion of Islamic banking which is increasingly expanding to all corners of Indonesia, so that Islamic banking is required to be able to implement its operations in accordance with sharia principles. The purpose of this research is to find and analyze Islamic Marketing and Trust in customer loyalty at PT. BPRS in Lampung Province. This research is a quantitative research with a questionnaire data collection tool that is distributed to customers of PT. BPRS in Lampung Province. The sample used in this study was 100 customers, with a purposivesampling data collection technique. Data analysis used in this research is simple linear regression data analysis. The results of this study found that there was an influence of Islamic marketing on customer loyalty in murabahah financing by 35.7%, there was an influence of trust in customer loyalty in murabahah financing by 20%. Therefore to maintain customer loyalty PT. BPRS throughout Lampung Province can carry out various options such as improving service quality, increasing satisfaction, perceived value, E-Servqual and using mobile banking.